The Impact of Providing Android-Based Illustrated Videos on Knowledge of Stunting Prevention in Women of Childbearing Age - Nimrayani; Nurhudayat Trianinsi; Eka Sari Ridwan (Jurnal Gizi dan Kesehatan Keluarga, 2025)
Indonesia is struggling with a serious malnutrition problem. Poor nutrition, starting from pregnancy, has caused many problems for both mothers and babies. One of these problems is stunting. To prevent and reduce stunting cases, the Caile District Government has been actively working with different groups, strengthening the roles of villages, providing comprehensive nutrition programs, and involving various sectors in planning and monitoring activities. This study aimed to find out how providing Android-based illustrated videos can improve the knowledge of women of childbearing age about preventing stunting in the UPT Caile Community Health Center area in 2024. We used a quasi-experimental design with a pre-test and post-test to conduct this study. The study included all women of childbearing age who visited the health centre for TT immunization or premarital screening from October to December 2023. Out of 42 women, 30 were selected for the study. The results showed that the women's knowledge about preventing stunting improved significantly after watching the videos. Mothers need to develop a habit of reading and seeking information about becoming a mother.